Retrospective Analysis of the Results and Causes of Penetrating Keratoplasty with Native Donor Material in a Multidisciplinary Hospital (Along the Example of MCOC Botkin Hospital) - G. Sh. Arzhimatova; E. A. Salikhov; M. Yu. Shemyakin; A. I. Ibraimov (Oftalʹmologiâ, 2023)
Penetrating keratoplasty (PC) is an operation of choice for urgent and planned conditions of the pathologic cornea. Moscow City Ophthalmological  Center “Botkin Hospital” together with the Moscow Coordination Center for  Organ Donation) over the past five years, has been performing corneal transplants using native donor material. In the available literature sources, we could not find publications devoted to conducting PC with native donor material in a multidisciplinary hospital. This publication analyzes our own experience of end-to-end corneal transplantation with native donor material for the period from 2018 to 2022.